DESAIN LAPORAN KEUANGAN PADA UMKM JAVIER PARFUME - Lena, Frasty Kesya; Pasuhuk, Aurellia Tiffany Casey; Dewi, Agung Eka; Sahabati, Regina Felicitas; Walesasi, Eglesia J (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Parfume MSMEs are businesses that can be considered MSMEs that are in great demand by the public because they are considered popular and profitable and can be started on a small scale and affordable capital. UMKM Javier Parfume is one of the businesses that provides various variants of parfume scents. Business actors in Javier Parfume MSMEs have not made financial reports according to standards, where they only make financial reports manually which only record cash expenditures and receipts. The urgency of this research is to design financial reports according to standards (SAK EMKM) using Microsoft Excel-based applications. This research uses a qualitative descriptive research approach. Data sources were conducted through interviews, observations, and literature studies. The benefits for business actors are to get financial reports according to standards and detailed financial information, for researchers can increase knowledge about financial reports and for institutions to add partners in the development of science and technology.